Immobilization of Analgetic AB-101 into Calcium Alginate Gels - R.M. Iskakov; E.O. Batyrbekov; B.A. Zhubanov; Y.Y. Fomicheva; V. K. Yu; K.D. Praliev; D.K. Berlin (Eurasian Chemico-Technological Journal, 2002)
A new analgetic drug AB-101 has been immobilized into Ca2+-alginate gel beads with average diameter of 1 mm. A series of the alginate gel contains with various mannuronic/guluronic (M/G) ratios has been chosen to control the diffusion of the drug. Release of the drug from the alginate gel beads into physiological solutions consisting of sodium ions has been examined. A discontinuous time of the Fickian diffusion of the drug depending on M/G ratio was followed by a burst release of the remaining drugs. The burst release was due to a swift disintegration of Ca2+-alginate with exchange on sodium ions. The preceding discontinuous lag time promotes a free dissociate exchange of sodium-calcium ions in M units, while the burst disintegration leads to fast dissociation of G units. The lag time can be control by M/G ratio of Ca2+-alginate gels. The lag time increases if a content of the M units decreases. The increase of M units was led to more extensive swelling of the gel beads. Such way could be promising for a controlled drug delivery or the use in implants with controlled drug effect.